THEORETICAL STUDY OF RELATIONSHIP BETWEEN LOCATIONS SELECTION AND LOW INCOME COMMUNITIES IN INDONESIA - Ayuko Setyo Adiyanti; Ikaputra Ikaputra (ARSITEKTURA, 2019)
The location preference for each individual is different because influenced by various factors. Nowadays, various dynamics of these factors have changed and resulted in the displacement of housing to meet better living. This paper tries to explore various theoretical studies regarding the tendency of location selection by low-income communities. This theoretical study was compiled from various studies consisting of results of studies, and results of previous research publications related to the topic of this study. The research method is carried out by data processing techniques derived from literature studies, the discovery of important keywords and theoretical frameworks for the final part of the writing this paper. The factors that influence the choice of location selection between general public and low income communities are almost same but different priorities. Accessibility that makes it easier for residents to access various locations to be addressed is a priority in choosing location selection for the people, while low-income communities prioritize consideration of the distance of location selection to workplaces. Another low-income people choose to live in the downtown area for the convenience of living close to job providers, while others choose to live on the outskirts of the city with consideration of affordable land.